Worker mobility and productivity spillovers - Roope Ohlsbom (The Research Institute of the Finnish Economy (ETLA), 2022)
Using linked employer-employee data from Finland, we examine the mobility of workers between establishments as a source of productivity-affecting knowledge spillovers. We find evidence that hiring workers from more productive establishments leads to higher productivity in the following year. For an average establishment, this productivity increase amounts to 0.45 percent in our most conservative estimate. The observed productivity gains hold for a variety of specifications, and changes in the receiving establishments' human capital stock are ruled out as an explanation.
Keywords: D22; D62; J21; J24; J62; L25; 330; Worker mobility; Spillovers; Productivity; Human capital